Toward the understanding of the molecular basis for the inhibition of COX-1 and COX-2 by phenolic compounds present in Uruguayan propolis and grape pomace. Issue 12 (1st December 2016) - Paulino, Margot; Alvareda, Elena; Iribarne, Federico; Miranda, Pablo; Espinosa, Victoria; Aguilera, Sara; Pardo, Helena
Abstract : Propolis and grape pomace have significant amounts of phenols which can take part in anti-inflammatory mechanisms. As the cyclooxygenases 1 and 2 (COX-1 and COX-2) are involved in said mechanisms, the possibility for a selective inhibition of COX-2 was analyzed in vitro and in silico . Propolis and grape pomace from Uruguayan species were collected, extracted in hydroalcoholic mixture and analyzed. Based on phenols previously identified, and taking as reference the crystallographic structures of COX-1 and COX-2 in complex with the commercial drug Celecoxib, a molecular docking procedure was devised to adjust 123 phenolic molecular models at the enzyme-binding sites. The most important results of this work are that the extracts have an overall inhibition activity very similar in COX-1 and COX-2, i.e. they do not possess selective inhibition activity for COX-2. Nevertheless, 10 compounds of the phenolic database turned out to be more selective and 94 phenols resulted with similar selectivity than Celecoxib, an outcome that accounts for the overall experimental inhibition measures. Binding site environment observations showed increased polarity in COX-2 as compared with COX-1, suggesting that polarity is the key for selectivity. Accordingly, the screening of molecular contacts pointed to the residues: Arg106, Gln178, Leu338, Ser339, Tyr341, Tyr371, Arg499, Ala502, Val509, and Ser516, which would explain, at the atomic level, the anti-inflammatory effect of the phenolic compounds. Among them, Gln178 and Arg499 appear to be essential for the selective inhibition of COX-2.